FORCED SEXUAL RELATIONSHIP HUSBAND WIFE in ISLAM: MAQĀṢID SHARĪ'AH PERSPECTIVE - Eki Resa Firiski (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2021)
This article is the result of library research. The direction of this research discussion is how the Islamic religion addresses the issue of forced sexual intercourse between husband and wife. This article discusses vis a vis between maqāsid sharī'ah and Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Claim of this research is the forced sexual intercourse of husband and wife according to Law Number 23 of 2004 is in line with the objectives of Islamic law (maqashid syar'iah) which is to protect tauhid/monotheism (hifd al din) men and women. The equality of relations between men and women is contained in the teachings of mu'āsharah bi al-ma'rūf (good association). Sexual violence can occur in both husband and wife. If the husband forces sexual intercourse, then it is prohibited. Vice versa, if the wife refuses to have sex without a syar'i reason, then this is also prohibited. not allowed. According to Islamic law, sexual violence can be punished with a finger of ta'zir sanction. Islam forbids acts of forced sexual intercourse as well as violence by husbands against their wives. And vice versa. Islam came with the main mission of realizing the benefit of all creatures, men and women. Islam teaches equal and equal sexual relations between husband and wife. Keywords: forced sexual intercourse, maqashid shari'ah Abstrak Artikel ini adalah hasil dari penelitian kepustakaan. Arah diskusi penelitian ini adalah bagaimana agama islam menyikapi isu pemaksaan hubungan seksual suami istri. Artikel ini mendiskusikan vis a vis antara maqāsid sharī’ah dan Undang-Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga. Klaim penelitian ini adalah bahwa pemaksaan hubungan seksual suami istri menurut Undang-Undang Nomor 23 Tahun 2004 selaras dengan tujuan syariat islam (maqashid syar’iah) yaitu melindungi ketauhidan (hifd al dīn) laki-laki dan perempuan. Kesetaraan relasi laki-laki dan perempuan tertuang dalam ajaran mu’āsharah bi al-ma’rūf. Kekerasan seksual dapat terjadi pada istri maupun suami. Jika suami memaksa hubungan seksual, maka itu dilarang. Demikian pula sebaliknya, jika istri menolak berhubungan tanpa alasan yang syar’i, maka ini juga dilarang. tidak diperbolehkan. Menurut hukum Islam, kekerasan seksual dapat dipidana dengan sanksi jarimah ta’zir. Islam melarang tindakan pemaksaan hubungan seksual juga kekerasan yang dilakukan suami atas istri.dan juga sebaliknya. Islam datang dengan misi pokok mewujudkan kemaslahatan bagi seluruh makhluk, laki-laki maupun perempuan. Islam mengajarkan relasi seksual suami–istri yang sejajar dan setara. Kata Kunci : pemaksaan hubungan seksual, maqashid syari’ah